Analisis Penerimaan Teknologi Virtualisasi Museum Pada Platform SIMVONI Menggunakan UTAUT - Achmad Bias Firmansyah; Tri Lathif Mardi Suryanto; Arista Pratama (STMIK Budi Darma, 2023)
The COVID-19 pandemic has paralyzed various sectors both domestically and abroad. The rapid spread of the virus has led the government to issue restrictions on public activities and the closure of various public places, including museums which are part of the tourism sector. This has disrupted museum activities, requiring alternative ways for the public to enjoy museum collections. Therefore, the adoption of virtual tour technology can be implemented to solve this problem and an evaluation is needed to see the acceptance of this technology by the public. This research was conducted to explore the factors that influence the acceptance of a web-based virtual tour called SIMVONI using the Unified Theory of Acceptance and Use of Technology (UTAUT) method and to recommend improvements to the SIMVONI developers based on the research results. The data obtained will be analyzed using SEM-PLS) The results of this research are that the significantly influential factors are social influence and intention to use, and some other factors that are not significantly influential are performance expectancy, effort expectancy, facilitating condition, and interaction.The impact of this acceptance is that users tend to share their experiences using the new technology with people around them and it can increase their desire to visit the museum in person after experiencing the virtual tour service. This can be utilized by SIMVONI developers as a promotional strategy with User Generated Content (UGC) techniques such as asking users to share their experiences or testimonials in the form of photos, videos, or writing